Should Blood Blend with Milk : A History of Incitement to Vengeance in Arabic Poetry from Jahili Voice to Militant Jihadist Verse - Fakhro, Dena (Islamic Thought and History, 2025)
In Should Blood Blend with Milk , Dena Fakhro offers an account of Middle Eastern conflicts told from the perspective of Arabic poetry and the blood feud. Far from being confined to antiquity, verse promoting bloody retribution continues to be generated by armed groups, whereas among moderates there are lampoons which instead serve as protest and warning. Traditionally, blood vengeance is a requirement for settling scores and restoring honour to injured parties. By making wide use of poems ranging from pre-Islamic Arabia, the medieval caliphates and the modern map of the Middle East, Fakhro proves these texts belong to an epic continuum, employing recurrent language, while contextualising revenge as an aspect of sectarianism, border conflict between empires, anti-colonial resistance, and militant jihadism.